Metasurfaces with Fano resonances for directionally selective thermal emission. Issue 49 (20th July 2016) - Sakr, Enas; Dimonte, Deanna; Bermel, Peter
ABSTRACT: Thermal emission impacts a wide variety of applications, including thermophotovoltaics, photovoltaics, photon-enhanced thermionic emission, selective solar absorption, incandescent lighting, and spectroscopy. Ordinary structures generally emit a broad range of wavelengths, angles, and polarizations. However, highly selective thermal emission has potential to greatly improve performance in many of these applications. While prior work has explored a wide range of structures to provide some degree of control of one or more of these attributes, there is an ongoing challenge in combining readily-fabricated, simple structures made of appropriate (e.g., heat-resistant) materials with the desired functionality. Here, we will focus on using metasurfaces in conjunction with refractory materials as a platform for achieving selective control of emission. These structures are built from sub-wavelength elements that support localization of surface plasmon polaritons or electromagnetic resonant modes with appropriate attributes. Modeling is performed using rigorous coupled wave analysis (RCWA), plus Kirchhoff's law of thermal radiation, which is further validated using finite-difference time domain (FDTD) simulations and coupled-mode analysis. Such structures can be considered arbitrarily directional sources that can be carefully patterned in lateral directions to yield a thermal lens with a designed focal length and/or concentration ratio; the benefit of this approach is that it can enhance the view factor between thermal emitters and receivers, without restricting the area ratio or separation distance. This design and modeling platform is then applied to exclude thermal radiation over a certain range of angles. In this work, we study the effect of controlling the angular width and direction on the view factor, and we explore angular dependence of these angular selective structures.